A new species of Neohydatothrips (Thysanoptera: Thripidae) from India - Rachana, R.r. (Zootaxa, 2021)
With 120 described species (ThripsWiki 2020) Neohydatothrips is the most species-rich genus in the Thripidae subfamily Sericothripinae. Although widely distributed almost 70% of the species are from the New World (Lima & Mound 2016), with only seven species recorded from India (Rachana & Varatharajan 2017). The biology of most species in the genus remains unknown, but they apparently feed and breed on the leaves and/or flowers of various unrelated plants. A few species are economically important as plant pests as well as virus vectors, such as N. variabilis (Beach) (Zhou & Tzanetakis 2013; Lima & Mound 2016; Han et al. 2019). N. samayunkur (Kudo) is a pest on flowers and leaves of Tagetes spp. in many countries including India (Nakahara 1999; Bhatti et al. 2003). Even though N. gracilipes (Hood) was described originally as damaging cotton in Mexico, it is associated with weedy species of Sida in several countries including central India (Lima & Mound 2016). In southern China, N. flavicingulus Mirab-balou, Tong & Yang is reported as damaging leaves of Manglietia fordiana. In California, avocado crops are sometimes damaged by N. burungae (Hood) and this species is also recorded as distorting the young leaves of Passiflora in Colombia (Mound et al. 2019). N. gracilicornis (Williams) is reported as damaging Pinaceae and Betulaceae in Spain and South Italy (Marullo 2009). The purpose of this article is to describe a new species from India that was collected in the flowers of Jasminum sambac (Oleaceae) in Assam, northeastern India. A detailed structural diagnosis of this genus is provided by Masumoto and Okajima (2020).